Dynamics of Darul Dakwah wal Irsyad Education Institute - Taufik, Muhammad; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the dynamics of Darud Dakwah Wal Irsyad Education Institute. This study uses quantitative research. The data used in this research is secondary data. Data obtained were obtained from literature studies or literature studies from articles and books. Data analysis was performed using content analysis. Based on the results presentation of the literature study, it can be concluded that the dynamics of DDI educational institutions can be summarized as follows: 1) There are 800 Madrasas in Indonesia. Education is general in nature, consisting of DDI Islamic Kindergarten (TKI) to DDI Islamic Senior High School (SMAI). Education is Fanniyah in nature which consists of: DDI Islamic Community Schools (SKI), DDI Islamic Trade Courses (KDI), DDI Islamic Teacher Schools (SGI), DDI Islamic Kindergarten Teacher Schools (SGTKI), DDI Islamic Boarding Schools (SKTI); 2) 50 DDI Islamic Boarding Schools throughout Indonesia, 36 in South Sulawesi each, 3 in Central Sulawesi, 3 in Southeast Sulawesi, 2 in Gorontalo, 2 in East Kalimantan, 1 in South Kalimantan, 1 in Riau, one fruit in East Java, one fruit in Timika, one fruit in Jayapura, and one fruit in Biak; 3) For tertiary institutions, fourteen DDI assisted units, 1 STAI in Barru, 1 STAI in Pare-Pare, 1 STAI and STKIP in Pinrang, 3 STAI in Polmas (1 STAI, 1 STKIP, 1 STIP), 1 STAI in Sidrap, 1 STAI in Maros, 1 STAI in East Kalimantan, 1 STAI in Makassar, 1 STAI in Jeneponto, 1 STAI in Majene, 1 STAI in Pangkep, and 1 STAI and STKIP in Mamuju. Madrasas abroad, especially in Malaysia, have not submitted their reports to PB-DDI, so data collection cannot be carried out. Based on the results above, it can be concluded that DDI is developing in the field of education.